analisis Analisis Pengaruh Dimensi Budaya Terhadap Penggunaan Aplikasi Capcut Menggunakan UTAUT2 - Ariyansir, Sigit; Syaifullah; Khairil Ahsyar, Tengku; Jazman, Muhammad; Marsal, Arif (AI Society & STMIK Indonesia, 2024)
This research aims to determine the factors that influence the intention and use of the Capcut application, using Hofstede's extended UTAUT2 model with cultural variables. Data was collected through observation, interviews, document review and questionnaires. The analytical method used is PLS-SEM, with external models, internal models and hypothesis testing. The research results show that of the many hypotheses tested, only H3 (social influence on behavioral intentions), H7b (habits on usage behavior) and H14 (passion/restraint usage behavior) were accepted. Other hypotheses, such as performance expectations, effort expectations, and other cultural dimensions, did not show significant influence on usage intentions and behavior. In conclusion, habitual factors and social influence are the main drivers for adopting the Capcut application, while other factors do not have much influence in the context of this research